2021
DOI: 10.1590/1980-5373-mr-2020-0472
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Fracture Toughness with Solution Annealing Temperature in 18Ni Maraging 300 Steel

Abstract: Maraging steels are a class of ultra high strength steels of special importance due to their extremely high mechanical strength and good toughness. In this work, the effects of the solution annealing temperature on the mechanical properties of the maraging 300 steels were evaluated, in order to maximize the toughness without considerable detriment of the mechanical strength. Five solution annealing temperatures were evaluated. The characterization of the mechanical properties was done by tests of Rockwell C ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…These results regarding grain size are consistent with findings reported by other researchers [66,67]. Lima et al [68] observed that the growth rate of prior austenite grain size is relatively slow between 1133 and 1273 K and increases significantly above 1423 K, with grain size values ranging from approximately 8 µm at 1133 K to 164 µm for the 300-grade maraging steel solution-annealed at 1423 K. Additionally, Lima et al noted that martensitic plates are more equiaxed up to 1133 K and transform into martensitic blocks at a solution annealing temperature of 1237 K, characterized either by the same orientation or blocks separated by high-angle boundaries [69]. The Vickers hardness values for the samples STed at 1123 and 1373 K are identical in this study, both measuring 561 HV.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…These results regarding grain size are consistent with findings reported by other researchers [66,67]. Lima et al [68] observed that the growth rate of prior austenite grain size is relatively slow between 1133 and 1273 K and increases significantly above 1423 K, with grain size values ranging from approximately 8 µm at 1133 K to 164 µm for the 300-grade maraging steel solution-annealed at 1423 K. Additionally, Lima et al noted that martensitic plates are more equiaxed up to 1133 K and transform into martensitic blocks at a solution annealing temperature of 1237 K, characterized either by the same orientation or blocks separated by high-angle boundaries [69]. The Vickers hardness values for the samples STed at 1123 and 1373 K are identical in this study, both measuring 561 HV.…”
Section: Microstructurementioning
confidence: 99%
“…Regarding the origins of microcracks in the martensitic microstructure of maraging steels, Fanton et al [51] suggested the presence of an oxidized layer formed during welding passes. Lima et al reported the formation of several precipitation particles, such as TiC [69] and Ni 3 Ti [68], at the grain boundary during heat treatment. Viswanathan et al [18,19] observed that maraging material becomes softer due to the occurrence of the retained austenite phase.…”
Section: Crack Propagation Behavior In Hazmentioning
confidence: 99%